Pengaruh Implementasi Green Banking, Risiko Likuiditas, dan Risiko Kredit, Terhadap Kinerja Keuangan Sektor Perbankan - Alya Ghania Rahma; Marita Marita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the impact of Green Banking implementation, Liquidity Risk, and Credit Risk on the financial performance of banks in Indonesia in the period 2023–2024, taking into account the increase in sustainable practices and existing global challenges. This study uses a quantitative method with secondary data obtained from sustainability reports and financial reports, with a total of 89–92 data points after removing outliers. The analysis was conducted using multiple linear regression on three financial performance indicators, namely Return on Assets (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR). The results show that, simultaneously, all independent variables have a significant effect on the three financial performance indicators. Partially, green banking has a positive effect on financial performance. Liquidity risk also has a positive effect on financial performance. On the other hand, credit risk has a negative effect on financial performance. Overall, this study concludes that green banking practices and risk management can affect financial performance, although their contribution to financial performance variation is still limited, so more optimal sustainability and risk control strategies are needed in the future.